Plasma tau is increased in frontotemporal dementia - Foiani, Martha S (J Neurol Neurosurg Psychiatry, 2018)
BACKGROUND: Frontotemporal dementia (FTD) is a heterogeneous neurodegenerative disorder presenting clinically with personality change (behavioural variant FTD (bvFTD)) or language deficits (primary progressive aphasia (PPA)). About a third of FTD is familial with mutations in GRN, MAPT and C9orf72 being the major genetic causes. Robust biomarkers of the underlying pathology are still lacking in FTD with no markers currently being able to distinguish those with tau and TDP-43 inclusions during life. METHODS: This study used an ultrasensitive single molecule methodology to measure plasma tau concentrations in 176 participants: 71 with bvFTD, 83 with PPA and 22 healthy controls. The patient group included 36 with pathogenic mutations in either MAPT (n=12), GRN (n=9) or C9orf72 (n=15). Group comparisons were performed between clinical and genetic groups and controls using a linear regression model with bias-corrected bootstrap CIs. Correlative analyses were performed to investigate associations with measures of disease severity and progression. RESULTS: Higher plasma tau concentrations were seen in bvFTD (mean 1.96 (SD 1.07) pg/mL) and PPA (2.65 (2.15) pg/mL) compared with controls (1.67 (0.50) pg/mL). Investigating the PPA group further showed significantly higher levels compared with controls in each of the PPA subtypes (non-fluent, semantic and logopenic variants, as well as a fourth group not meeting criteria for one of the three main variants). In the genetic groups, only the MAPT group had significantly increased concentrations (2.62 (1.39) pg/mL) compared with controls. No significant correlations were seen with cross-sectional or longitudinal brain volumes, serum neurofilament light chain concentrations or disease duration. CONCLUSION: Plasma tau levels are increased in FTD in all clinical groups, but in the genetic subtypes only in MAPT mutations, the group of patients who definitively have tau pathology at postmortem. Future studies will be required in pathologically confirmed cohorts to investigate this association further, and whether plasma tau will be helpful in differentiating patients with FTD with tau from those with other pathologies.